Atypical presentation of primary intraocular lymphoma. Issue 1 (December 2016) - Komatsu, Koji; Sakai, Tsutomu; Kaburaki, Toshikatsu; Tsuji, Hideki; Tsuneoka, Hiroshi
Abstract Background In 2014, Pang et al. reported three cases with vitelliform submaculopathy as a preceding lesion of primary intraocular lymphoma (PIOL). Here, we report a case with an atypical presentation of PIOL who initially presented with vitelliform submaculopathy, vitreous haze and preripheral retinal focus. Case presentation A 73-year-old female initially visited another hospital with a chief complaint of acute reduced vision in the right eye. Funduscopic examination of the right eye showed a yellowish retinal lesion at the fovea with vitreous haze and retinal foci scattered in the peripheral region. Spectral-domain optic coherence tomography (SD-OCT) revealed a hyperreflective subretinal debris above the retinal pigment epithelium (RPE) at the fovea, suggesting vitelliform submaculopathy. Vitrectomy was performed to improve visualization of the retinal lesions and for examination of PIOL. Vitreous cytology was class III and cytokine analysis of vitreous fluid showed increased IL-10 and an IL-10/IL-6 ratio >1, suggesting PIOL. Thereafter, there was a sub-RPE infiltration of presumed lymphoma in the nasal retina, and PCR analysis of anterior chamber fluid indicated IgH gene rearrangement, leading to diagnosis of PIOL. Three months later, there was complete disappearance of the vitelliform submacular lesion, with resultant disruption and thinning of the outer retinal layers on SD-OCT images. Conclusions Clinicians should be aware of atypical manifestations of PIOL such as vitelliform submaculopathy and peripheral retinal foci with vitreous haze. The patient's unusual funduscopic changes are findings that have not reported in patients with PIOL.